Ratio Legis For The Establishment Of a State Audit Board - Listia Rahmawati Bumulo (Estudiante Law Journal, 2020)
The purpose of this study is to find out the ratio legis or the history of the establishment and development of the BPK. The method used in this research was normative research and the type of approach used was the statute approach, conceptual approach, and case approach. Legal material analysis techniques in this research used a systematic interpretation method. The results of the study showed that the importance of regulation related to financial matters and the State Audit Board has been realized by the nation's founders since the beginning of independence. At the beginning of the establishment of the State Audit Board, this institution still used the laws and regulations of the Dutch East Indies which became the legal basis for carrying out the duties of the Algemeene Rekenkame, namely ICW and IAR. However, as the government process in Indonesia progresses, the government also designs and establishes regulations related to the State Audit Board. The more updated and strengthened regulations related to the BPK were because the management of state finances is very important and is the most basic thing in realizing a clean government. The government should also expand and provide full support to BPK to make policy regulations that support the optimization of BPK's role as an independent institution so that BPK has more flexibility and authority to be able to realize its control function.Keywords: Authority; Government, Ideal